Identification of dopaminergic neurons that can both establish associative memory and acutely terminate its behavioral expression - Schleyer, Michael; Weiglein, Alice; Thoener, Juliane; Strauch, Martin; Hartenstein, Volker; Weigelt, Melisa Kantar; Schuller, Sarah; Saumweber, Timo; Eichler, Katharina; Rohwedder, Astrid; Merhof, Dorit; Zlatic, Marta; et al. (Journal of Neuroscience, 2020)
An adaptive transition from exploring the environment in search of vital resources to exploiting these resources once the search was successful is important to all animals. Here we study the neuronal circuitry that allows larval Drosophila melanogaster of either sex to negotiate this exploration-exploitation transition. We do so by combining Pavlovian conditioning with high-resolution behavioral tracking, optogenetic manipulation of individually identified neurons, and EM data-based analyses of synaptic organization. We find that optogenetic activation of the dopaminergic neuron DAN-i1 can both establish memory during training and acutely terminate learned search behavior in a subsequent recall test. Its activation leaves innate behavior unaffected, however. Specifically, DAN-i1 activation can establish associative memories of opposite valence after paired and unpaired training with odor, and its activation during the recall test can terminate the search behavior resulting from either of these memories. Our results further suggest that in its behavioral significance DAN-i1 activation resembles, but does not equal, sugar reward. Dendrogram analyses of all the synaptic connections between DAN-i1 and its two main targets, the Kenyon cells and the mushroom body output neuron MBON-i1, further suggest that the DAN-i1 signals during training and during the recall test could be delivered to the Kenyon cells and to MBON-i1, respectively, within previously unrecognized, locally confined branching structures. This would provide an elegant circuit motif to terminate search on its successful completion.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Dopamine; Exploration-exploitation; Mushroom body; Optogenetics; Reinforcement; Search